2005
DOI: 10.1097/01.icl.0000146320.64438.8c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preservative-Free Artificial Tears on the Antimicrobial Activity of Human ??-Defensin-2 and Cathelicidin LL-37 In Vitro

Abstract: Purpose. Human β-defensin-2 (hBD-2) and cathelicidin LL-37 are salt-sensitive cationic antimicrobial peptides expressed by ocular surface epithelia. The goal of this study was to investigate the effect of preservative-free artificial tears on hBD-2 and LL-37 antimicrobial activity against Pseudomonas aeruginosa.Methods. P. aeruginosa was incubated with hBD-2 or LL-37 in the absence or presence (70% vol/ vol) of different preservative-free artificial tears-Visine Tears (300 mOsm/kg), Tears Naturale Free (261 mO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Reversible binding of the peptides to anionic substances present in the tears is a possibility, as has been suggested for loss of b-defensin antimicrobial activity in the presence of carboxymethylcellulose (an anionic molecule)-containing artificial tear solutions. 19 Likely candidates in tear fluid include the anionic lipocalins and mucins. However, as human tear fluid is composed of hundreds of different molecules, many yet to be definitively identified, there may be several other components that can potentially interfere with defensin antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Reversible binding of the peptides to anionic substances present in the tears is a possibility, as has been suggested for loss of b-defensin antimicrobial activity in the presence of carboxymethylcellulose (an anionic molecule)-containing artificial tear solutions. 19 Likely candidates in tear fluid include the anionic lipocalins and mucins. However, as human tear fluid is composed of hundreds of different molecules, many yet to be definitively identified, there may be several other components that can potentially interfere with defensin antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…191,192,202 However, it has been observed that both hBD-2 and LL-37 lose their ability to kill P. aeruginosa in the presence of carboxymethylcellulose-containing artificial tears in vitro, possibly adding to apparent detrimental effects of artificial tear solutions on ocular surface immunity. 230 Clinically, we often observe that dry eye patients use artificial tear solutions several times per day, which may itself contribute to the flushing out of pathogenic microbes.…”
Section: Dry Eye Treatment and Modulation Of Risk For Keratitismentioning
confidence: 99%
“…In addition to recognizing pathogens and producing proinflammatory cytokines and chemokines, the corneal epithelium is also known to function in the innate immune response through the secretion of antimicrobial peptides [109][110][111][112][113][114][115][116]. Although most β-defensins are typically constitutively expressed, human β-defensin-2 (hBD-2) is remarkable in that it is inducible in a variety of epithelial cell types including those of the cornea [115,116].…”
Section: Role Of Tlrs In Secretion Of Anti-microbial Peptides (Defensmentioning
confidence: 99%